Reimagining Nursing Competency Evaluation: Clinical Assessors’ Readiness and Adaptation to Digital Assessment Systems in a Provincial Hospital Setting - Aam Amalia; Asep Setiawan; Setiawati Setiawati; Blacius Dedi; Gunawan Irianto (STIKep PPNI Jawa Barat, 2025)
Background: Clinical competency assessment is a core component of nursing governance and professional development. In many Indonesian hospitals, competency evaluations remain predominantly paper-based, resulting in administrative inefficiencies and limited data traceability. The implementation of the SICAKEP (Sistem Informasi dan Pencatatan Keperawatan) digital application at RSUD Welas Asih, West Java, represents an important step toward modernizing assessment processes; however, assessors’ experiences during this transition have not been fully explored. Objective: This study aimed to explore the lived experiences of clinical nurse assessors in conducting manual and digital (SICAKEP-based) competency assessments in a provincial teaching hospital in West Java, Indonesia. Methods: A qualitative descriptive phenomenological design grounded in a constructivist paradigm was employed. Four certified clinical nurse assessors with experience in both manual and digital assessments were recruited using purposive and snowball sampling. Data were collected through in-depth semi-structured interviews, brief observations, and document reviews between March and May 2025. Data analysis followed Colaizzi’s seven-step method, supported by reflexive journaling and member checking to enhance credibility. Results: Five themes emerged: adaptation to new assessment roles, multidimensional implementation barriers, constraints related to time and readiness, competency assessment as a driver of professionalism and quality, and transformation from manual to digital systems. Digital assessment improved efficiency and transparency but required stronger digital literacy and infrastructure support. Conclusion: Digital competency assessment represents a meaningful advancement in nursing governance, though sustained institutional support is essential to optimize its implementation